The Effect of Endurance Exercise Training on the Balance of Perinatal Stressed Parkinson Rats - S Azizi; A Movahedi; E Arabameri; A Ghasemi (Armaghane Danesh Bimonthly Journal, 2019)
Background & aim: Parkinson's disease is a disorder in the nervous system due to the degeneration of dopaminergic neurons. Dopaminergic system is susceptible to neurological disorders caused by exposure to stressors early. Positive experiences are one of the most powerful treatments to increase neuroplasticity and motor function at any time of life. The purpose of the present study was to investigate the effect of pre-treatment endurance training on the balance of Parkinson's rats with perinatal stress.